A Novel Formation Creation Algorithm for Heterogeneous Vehicles in Highway Scenarios: Assessment and Experimental Validation. Issue 2 (2020) - Zambelli, Massimo; Carulli, Paola; Steinberger, Martin; Horn, Martin; Ferrara, Antonella
Abstract: In this paper a novel algorithm for the on-line creation of formations of heterogeneous vehicles is proposed for highway traffic scenarios. A two-step iterative distributed strategy is formulated which relies on Dynamic Programming and trajectory tracking. Only position measurements and basic communication capabilities for global coordination are required, while scalability is guaranteed by the underlying structure of the algorithm. In addition, spatial and velocity constraints are taken into account. The presented concept forms the basis for more sophisticated formation creation controllers. Results obtained in experiments with automated small-scale trucks show the underlying validity and practical feasibility of the algorithm.